Conversion of Waste Tire Rubber into High-Value-Added Carbon Supports for Electrocatalysis. Issue 14 (1st January 2018) - Hood, Zachary D.; Yang, Xuan; Li, Yunchao; Naskar, Amit K.; Chi, Miaofang; Paranthaman, M. Parans
Abstract : Carbon supports are vital for a wide range of electrochemical reactions, yet the production of useful carbon supports largely relies on costly precursors and fabrication methods. Here, we present a new economical process to fabricate carbon-based supports for electrocatalysts using recycled tire rubber as the main feedstock. Using the oxygen reduction reaction (ORR) as an example, we deposited Pt nanocubes on tire-derived carbon with different textural properties and surface chemistries. Our results show that Pt nanocubes are most effective toward the ORR when loaded onto tire-derived carbon with an increased electrochemically active surface area, a decreased average pore diameter, low sulfur content, and good crystallinity. These properties collectively allow for high dispersion of Pt nanocubes onto the tire-derived carbon support, and hence, increase the activity toward oxygen reduction. When benchmarked against a commercial carbon black support (Ketjen-300), the tire-derived carbon support achieved similar performance. Our results highlight an effective approach to converting waste tires into carbon supports for electrocatalysis.